The Efficacy of Dental Plaque Removal and Usefulness for Periodontal Tissue of a Sonic Toothbrush Equipped with Tapping Amplitude - Haruka, MIURA; Mariko, HAMADA; Masaya, YOSHIMINE; Hisahiro, KAMOI (The Japanese Journal of Conservative Dentistry, 2020)
Objective: Plaque control by daily brushing is important to prevent oral diseases. The usefulness of electric toothbrushes for effective plaque control has been demonstrated. In this study, the usefulness of a new electric toothbrush for removing plaque was evaluated from multiple aspects. Subjects and Method: The subjects were males and females, regardless of age, who had knowledge of and were able to perform the oral cleaning method, and met the study conditions. For the test teeth, 6 Ramfjord teeth (16, 21, 24, 36, 41, and 44 or alternative teeth) without restoration with marked plaque accumulation were used. For the tool, two types of sonic toothbrush, the new Doltz and the conventional Doltz (Panasonic), were used. First, to evaluate oral plaque removal, plaque was scored using the Rustogi Modification Navy Plaque Index before and after use of the sonic toothbrush. For statistical analysis, the Wilcoxon test was used. Then, to evaluate oral cleaning, the following evaluation items were measured before and after use of the toothbrush: probing depth (PD), bleeding on probing (BOP), and gingival index (GI). For statistical analysis, the Wilcoxon test was used. Results and Discussion: The plaque removal rate was higher in the conventional Doltz group than in the new Doltz group in all regions, but the differences between the two groups were not significant. On evaluation of periodontal pocket cleaning, the improvement rates of all parameters (PD, BOP, and GI) were higher in the new Doltz group than in the conventional Doltz group. In addition, significant differences were noted after use in all parameters on intra-group comparison (p<0.05). This study clarified that the new Doltz has greater improvement effects on periodontal tissue than the conventional Doltz; this may be due to the tapping amplitude newly added to the main unit of the new Doltz, which appropriately stimulates the gingiva, as well as the dense extra-fine toothbrush, which is optimal for periodontal pocket cleaning, exhibiting synergistic effects to improve the gingiva. Sonic toothbrushes are expected to be effective for plaque control to prevent caries and periodontal disease.